Impact of Farmers’ Livelihoods on Agricultural Carbon Emission Efficiency Under the Background of Population Urbanization: Evidence from China - Ming Chang; Xiaotong Li; Fei Li; Hesen Zhao (Agriculture)
In the context of China’s population urbanization, the quality and pattern of farmers’ livelihoods are undergoing significant changes. Reducing emissions and sequestering carbon in agriculture is a crucial pathway for China to achieve its “dual carbon” goals. How to balance low-carbon agricultural development with the changing livelihood patterns of farmers has become an important issue in China’s agricultural and rural development. This study examines the impact of farmers’ livelihoods on agricultural carbon emission efficiency and explores regional disparities based on panel data from 31 provinces and municipalities in China from 2002 to 2020. The findings are as follows: (1) The quality of farmers’ livelihoods in China is conducive to an improvement in agricultural carbon emission efficiency (ACEE). (2) From a national perspective, the higher the livelihood of non-farm employment in the region, the higher the agricultural carbon emission efficiency. The livelihood of agricultural production has a significantly negative correlation with agricultural carbon emission efficiency. (3) Improvement in the quality of farmers’ livelihoods (QFL) in the eastern and western regions has a significant positive impact on the efficiency of agricultural carbon emissions, and the impact is larger in the western region, while there is no statistically significant relationship in the central region. The reason for this difference may be that the migration of agricultural labor from the western region to the eastern region and the local urban employment of eastern farmers have led to this, while the migration and local urban employment of agricultural labor in the central region is relatively limited. This paper provides policy insights into promoting both farmers’ income growth and low-carbon agricultural production in a coordinated manner.